1985
DOI: 10.1007/bf00163589
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucracy and the divisibility of local public output

Abstract: Recent research has analyzed the issue of whether local government services are public or private in nature. In analyzing the determinants of local government spending both Bergstrom and Goodman (1973) and Borcherding and Deacon (1972) developed variants of the median voter model which permitted estimation of 'publicness' parameters in reduced form expenditure equations. In both studies the estimated parameter indicated that municipal services are divisible in consumption, a characteristic of private goods. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 16 publications
3
24
1
Order By: Relevance
“…When the extension of city boundaries results in an increase in population dq/dA .~ 0 as dq/dN .~ 0. We have shown elsewhere (Gonzalez and Mehay, 1985) that the relationship between per capita consumption of municipal services and population (dq/dn) depends on the publicness of the good and underlying cost conditions. Since there is considerable evidence (Bergstrom and Goodman, 1973;Borcherding and Deacon, 1972) against the only case when dq/dN < 0, we reject this possibility and conclude that all terms in (4) will be positive or zero so that d (T/N)/dA > 0.…”
Section: Annexation and Interjurisdictional Competitionmentioning
confidence: 99%
“…When the extension of city boundaries results in an increase in population dq/dA .~ 0 as dq/dN .~ 0. We have shown elsewhere (Gonzalez and Mehay, 1985) that the relationship between per capita consumption of municipal services and population (dq/dn) depends on the publicness of the good and underlying cost conditions. Since there is considerable evidence (Bergstrom and Goodman, 1973;Borcherding and Deacon, 1972) against the only case when dq/dN < 0, we reject this possibility and conclude that all terms in (4) will be positive or zero so that d (T/N)/dA > 0.…”
Section: Annexation and Interjurisdictional Competitionmentioning
confidence: 99%
“…This result was initially stated in the seminal median voter papers of Borcherding and Deacon (1972) and Bergstrom and Goodman (1973) and endorsed by other authors who developed bureaucratic approaches: Gonzalez and Mehay (1985) and Wyckoff (1988). Here, population is a rough indicator of "needs".…”
Section: Other Determinants Of Grant Designmentioning
confidence: 82%
“…The use of this method, however, has almost uniformly resulted in the counterintuitive conclusion that local public goods are actually pure private goods with respect to their crowding behavior. Gonzalez and Mehay (1985), for example, note that in addition to the original two articles, at least six subsequent studies have come to this conclusion. Borcherding, Bush, and Spann (1977) have argued that bureaucracy is to blame for these results.…”
mentioning
confidence: 99%
“…Under such a correlation, part of the extra spending in larger cities which is erroneously attributed to greater population by the BDBG approach is actually due to greater bureaucratic power in those larger cities. In a more recent paper, Gonzalez and Mehay (1985) have suggested that the presence of bureaucracy completely invalidates the BDBG approach, necessitating an alternative and less precise methodology to estimate the publicness of local public goods.In this paper I use a new, more exact model of bureaucratic influence to argue that bureaucracy cannot be responsible for the anomalous results found in the empirical literature. The paper demonstrates that: (1) if bureaucracies can alter the composition of spending in a community, they will push for local public goods which are close to the pure public good, rather than pure private good, extreme; and (2) if bureaucratic power is correlated with population, the estimated results will be biased toward the pure public good extreme.…”
mentioning
confidence: 99%
See 1 more Smart Citation